2007
DOI: 10.1080/09603100600771034
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying volatility and equity returns in Bangladesh stock market

Abstract: This article empirically examines the time-varying risk return relationship and the impact of institutional factors such as circuit breaker on volatility for the emerging equity market of Bangladesh [namely The Dhaka Stock Exchange (DSE)] using daily and weekly stock returns. The DSE equity returns show negative skewness, excess kurtosis and deviation from normality. The returns display significant serial correlation suggesting stock market inefficiency. The results also show a significant relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…However, they remain more conservative about their market risk assessment after volatility interruptions so this tranquillizing eect magnitude is comparable to midday auctions. These results are backed by Basher et al (2007) who nd price uncertainty after volatility interruptions to be sometimes increased or reduced. We therefore conclude that it is wrong to believe such interruptions would automatically initiate a return to smooth and orderly trading but it is dependent upon the auction's contribution.…”
Section: Determinants Of Price Discoverymentioning
confidence: 90%
See 1 more Smart Citation
“…However, they remain more conservative about their market risk assessment after volatility interruptions so this tranquillizing eect magnitude is comparable to midday auctions. These results are backed by Basher et al (2007) who nd price uncertainty after volatility interruptions to be sometimes increased or reduced. We therefore conclude that it is wrong to believe such interruptions would automatically initiate a return to smooth and orderly trading but it is dependent upon the auction's contribution.…”
Section: Determinants Of Price Discoverymentioning
confidence: 90%
“…Basher, Hassan, and Islam (2007) applied stock-wise GARCH volatility estimation, indicating that although some stocks are followed by decreased price uncertainty, others indicate signicantly increased price uncertainty. This dissent is further driven by the lack of a distinct causal coherence between the volatility interruption itself and subsequent market uncertainty levels.…”
Section: Introductionmentioning
confidence: 99%
“…In order to test whether CAPM is a good indicator of asset pricing in Bangladesh, Rahman, Baten, and Alam (2006) considered Fama and French (1992) methodology and found that the variables have a significant relationship to the stock return. Basher, Hassan and Islam (2007) found that the DSE equity returns show negative skewness, excess kurtosis and deviation from normality. There are some actions (Hussain, Chakraborty, & Kabir, 2008) which can improve the efficiency of the DSE market such as: ensuring asymmetric information among all investors, proper implication of rules of regulatory commission and introducing sophisticated means of investment and tools.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings GARCH (1,1) is found to be the best model. Reference [5] observed a significant negative relationship between conditional volatility and stock returns and attributed circuit breaker as a causal factor that contributed to the volatility of realized returns. Reference [30] examined a wide variety of GARCH models under different distributional assumption but models under Student-t distributional assumptions are found to be suitable for modelling volatility of Chittagong Stock Exchange (CSE).…”
Section: Literature Reviewmentioning
confidence: 99%